Business finance and banking / by Neil H. Jacoby ... and Raymond J. Saulnier ... - Jacoby, Neil H.; Saulnier, Raymond J. (New York : National Bureau of Economic Research, 1947)
This book endeavored to determine for recent years the general pattern of demand in the market for short-term and medium-and long-term business credit; it traced the structural changes that have occurred since 1900 in the business financial organization, especially in manufacturing and trade enterprises.
Includes index
usc 16/05/2017
Loans
Keywords: Credit; Banks and banking